2016
DOI: 10.1371/journal.pone.0157251
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Breast Cancer Potential of Quercetin via the Akt/AMPK/Mammalian Target of Rapamycin (mTOR) Signaling Cascade

Abstract: The Akt/adenosine monophosphate protein kinase (AMPK)/mammalian target of rapamycin (mTOR) pathway has emerged as a critical signaling nexus for regulating cellular metabolism, energy homeostasis, and cell growth. Thus, dysregulation of this pathway contributes to the development of metabolic disorders such as obesity, type 2diabetes, and cancer. We previously reported that a combination of grape polyphenols (resveratrol, quercetin and catechin: RQC), at equimolar concentrations, reduces breast cancer (BC) gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(54 citation statements)
references
References 53 publications
(71 reference statements)
5
49
0
Order By: Relevance
“…We also discovered that MDA-MB-231 cells treated with quercetin had a lower proportion of G1 phase cells and a higher proportion of G2/M phase cells compared to those not treated with quercetin ( Figure 3 ). These results are similar to those previously reported [ 25 ]. Quercetin-mediated cell cycle arrest in the G2/M phase is possibly associated with upregulation of cyclin D1, which has been reported in other cell lines [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 94%
“…We also discovered that MDA-MB-231 cells treated with quercetin had a lower proportion of G1 phase cells and a higher proportion of G2/M phase cells compared to those not treated with quercetin ( Figure 3 ). These results are similar to those previously reported [ 25 ]. Quercetin-mediated cell cycle arrest in the G2/M phase is possibly associated with upregulation of cyclin D1, which has been reported in other cell lines [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 94%
“…Our results are also in line with Li et al (84); the authors who also used NAR, to induce apoptosis in MDA-MB-231 cells. After QUE treatment, Choi et al (85) detected apoptosis in MDA-MB-453 cells, another TNBC line, similar to research by Rivera et al (86) and in line with our own results on different breast cancer cells.…”
Section: Discussionsupporting
confidence: 91%
“…2,3 Studies have shown that flavonoids can play its roles through many genes and pathways, for example, nuclear factor kappa B(NF-kB), phosphatidylinositol3'-kinase (PI3K), signal transducers and activators of transcription (STAT), and tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), to protect human health. [4][5][6] Quercetin(3,3′,4′,5,7-Pentahydroflavone,QE) is a typical flavonoid that shows significant effects on blocking the development of breast cancer, 7 ovarian cancer, 8 carcinoma of colon and rectum, 9 gastric cancer, 10 and hepatic cancer. Our previous studies have shown that quercetin could protect the liver from concanavalin A-induced acute hepatitis, ischemia reperfusion injury, and fibrosis.…”
Section: Introductionmentioning
confidence: 99%